2002
DOI: 10.1002/j.2168-9830.2002.tb00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing Faculty‐Student Dialogue, Deep Learning and Creativity through Journal Writing Exercises

Abstract: One of the most difficult endeavors in the engineering curriculum is encouraging students to develop creative, independent thought and a deep level of understanding. To achieve these results, we incorporate journal writing exercises into the curriculum of a core chemical engineering course, ChE 363 (Unit Operations II: Separations) at the University of Texas at Austin. Students receive weekly prompts to develop analogies or thought experiments to describe fundamental concepts prior to discussion in lecture. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…"Since the analogies often describe real-life experiences, students feel closely connected to the discussion, which effectively promotes dialogue between the students and the instructor." (Korgel, 2002) In this study, students reported that the journals h elp ed th em d evel op deep er co n cep tu al understanding. The distinction between knowledgelevel learning and deeper conceptual understanding was also considered by Sharp, et al (1997) and Randolph (2000), who examined how writing activities can be used to engage students at all six levels of understanding described by Bloom's Taxonomy (Bloom, 1967).…”
Section: Reflective Writing Activities For Engineering Coursesmentioning
confidence: 77%
See 1 more Smart Citation
“…"Since the analogies often describe real-life experiences, students feel closely connected to the discussion, which effectively promotes dialogue between the students and the instructor." (Korgel, 2002) In this study, students reported that the journals h elp ed th em d evel op deep er co n cep tu al understanding. The distinction between knowledgelevel learning and deeper conceptual understanding was also considered by Sharp, et al (1997) and Randolph (2000), who examined how writing activities can be used to engage students at all six levels of understanding described by Bloom's Taxonomy (Bloom, 1967).…”
Section: Reflective Writing Activities For Engineering Coursesmentioning
confidence: 77%
“…Students are free to respond with illustrations, text, derivations, sample problems, etc." (Korgel, 2002) The instructor then chose 3-5 of the best analogies and presented them anonymously to the class, and extra credit was awarded to the student whose analogy was voted by the class as the "best". A primary benefit of the activity was the class discussion that preceded the vote.…”
Section: Reflective Writing Activities For Engineering Coursesmentioning
confidence: 99%
“…One of the most difficult endeavors in the engineering curriculum is encouraging students to develop creative, independent thought and a deep level of understanding [12]. One major goal in this HAB program is to prepare students for the engineering profession.…”
Section: Technical and Professional Developmentmentioning
confidence: 99%
“…In the HAB project, students participated in weekly lectures, seminars, and workshop aimed at enlightening them in issues and activities related to the engineering profession. One of the most difficult endeavors in the engineering curriculum is encouraging students to develop creative, independent thought and a deep level of understanding [6]. One major goal in this HAB program is to prepare students for the engineering profession.…”
Section: Technical and Professional Developmentmentioning
confidence: 99%